Juridical Review of The Sale and Purchase of Foundation Assets Reviewed from Law Number 16 of 2001 J.O Law Number 28 of 2004 Concerning Foundations (Universitas Muhammadiyah Surakarta, 2025)
A foundation is a legal entity that consists of separated assets and is intended to achieve specific goals in the social, religious, and humanitarian fields, which have no members. With the promulgation of the Law of the Republic of Indonesia on Foundations Number 16 of 2001 on August 6, 2001 which came into effect on August 6, 2002, it is hoped that efforts to realize legal certainty about Foundations in Indonesia can be realized. One of the foundation's wealth is sourced from Waqaf which is explained in Law No. 41 of 2004 concerning Waqf states that property that has been waqf is prohibited from being used as collateral, confiscated, granted, sold, inherited; Exchangeable; or transferred in the form of other transfer of rights. So in this study, the author tries to explain how the foundation is switched by buying and selling assets as happened at the IPHI Pedan Special Hospital. This descriptive research uses a normative legal research method that prioritizes secondary data and descriptive analysis. The results of this study show an explanation of the Buying and Selling of Foundation Assets in Review of Law No. 16 of 2001 Jo Law No. 28 of 2004 concerning Foundations.